[CuII(LISQ)˙−2] (H2L: thioether-appended o-aminophenol ligand) monocation triggers change in donor site from N2O2 to N2O(2)S and valence-tautomerism. Issue 5 (15th January 2019) - Rajput, Amit; Saha, Anannya; Barman, Suman K.; Lloret, Francesc; Mukherjee, Rabindranath
Abstract : The complex [Cu II (L ISQ )˙ − 2 ]·CH2 Cl2 and its 1e − oxidized form are synthesized and structurally characterized; temperature-induced equilibrium, involving [Cu II (L ISQ )˙ − (L IBQ ) 0 ](PF6 ) ⇌ [Cu I (L IBQ ) 0 2 ](PF6 ) is observed. Abstract : Using a potentially tridentate o -aminophenol-based redox-active ligand H2 L 1 (2-[2-(benzylthio)phenylamino]-4, 6-di- tert -butylphenol) in its deprotonated form, [Cu(L 1 )2 ] has been synthesized and crystallized as [Cu II (L 1 )2 ]·CH2 Cl2 (1 ·CH2 Cl2 ). A cyclic voltammetry experiment (in CH2 Cl2 ; V vs. SCE (saturated calomel electrode)) on1 ·CH2 Cl2 exhibits two oxidative ( E 11/2 = 0.20 V (peak-to-peak separation, Δ E p = 100 mV) and E 21/2 = 0.90 V (Δ E p = 140 mV)) and two reductive ( E 11/2 = −0.52 V (Δ E p = 110 mV) and E 21/2 = −0.92 V (Δ E p = 120 mV)) responses. Upon oxidation using a stoichiometric amount of [Fe III (η 5 -C5 H5 )2 ](PF6 ), 1 ·CH2 Cl2 yielded [Cu(L 1 )2 ](PF6 ) (2 ). Structural analysis (100 K) reveals that1 ·CH2 Cl2 is a four-coordinate bis(iminosemiquinonato)copper(ii ) complex (CuN2 O2 coordination), and that the thioethers remain uncoordinated. The twisted geometry of1 (distorted tetrahedral) results in considerable changes in the electronic structure, compared to well-known square-planar analogues. Crystallographic analysis of2 both at 100 K and at 293 K reveals that it is effectively a four-coordinate complex with a CuN2 OS coordination; however, a substantial interaction with the other phenolate O is observed. The metal–ligand bond distances and metric parameters associated with the o -aminophenolate rings indicate a valence-tautomeric (VT) equilibrium involving monocationic (iminosemiquinonato)(iminoquinone)copper(ii ) and bis(iminoquinone)copper(i ). Complex1 ·CH2 Cl2 is a three-spin system and a magnetic study (4–300 K) established that it has a S = 1/2 ground-state, owing to the strong antiferromagnetic coupling between the unpaired spin of the copper(ii ) and the iminosemiquinonate(1−) π-radical anion. Electron paramagnetic resonance (EPR) spectral studies corroborate this result. Complex2 is diamagnetic and the existence of VT in2 was probed using variable-temperature (248–328 K) 1 H NMR and EPR (100–298 K) spectral measurements and X-ray photoelectron spectroscopic studies at 298 K. Remarkably, modification of the well-studied 2-anilino-4, 6-di- tert -butylphenol by incorporation of a benzylthioether arm leads to the occurrence of VT in2 . The electronic structure of1 ·CH2 Cl2 and2 has been assigned using density functional theory (DFT) calculations at the B3LYP-D3 level of theory. Time-dependent (TD)-DFT calculations have been performed to elucidate the origin of the observed UV-VIS-NIR absorptions.